Comparing the accuracy of six intraoral scanners on prepared teeth and effect of scanning sequence - Diker, Burcu (J Adv Prosthodont, 2020)
PURPOSE: The aim of this study was to evaluate the accuracy of six recently introduced intraoral scanners (IOSs) for single crown preparations isolated from the complete arch, and to determine the effect of scanning sequence on accuracy. MATERIALS AND METHODS: A complete arch with right and left canine preparations for single crowns was used as a study model. The reference dataset was obtained by scanning the complete arch using a highly accurate industrial scanner (ATOS Core 80, GOM GmbH). Six different IOSs (Trios, iTero, Planmeca Emerald, Cerec Omnicam, Primescan, and Virtuo Vivo) were used to scan the model ten times each. The scans performed with each IOS were divided into two groups, based on whether the scanning sequence started from the right or left quadrant (n=5). The accuracy of digital impression was evaluated using three-dimensional analyzing software (Geomagic Studio 12, 3D Systems). The Kruskal Wallis and Mann-Whitney U statistical tests for trueness analysis and the One-way ANOVA test for precision analysis were performed (α=.05). RESULTS: The trueness and precision values were the lowest with the Primescan (25 and 10 µm), followed by Trios (40.5 and 11 µm), Omnicam (41.5 µm and 18 µm), Virtuo Vivo (52 and 37 µm), iTero (70 and 12 µm) and Emerald (73.5 and 60 µm). Regarding trueness, iTero showed more deviation when scanning started from the right (P=.009). CONCLUSION: The accuracy of digital impressions varied depending on the IOS and scanning sequence used. Primescan had the highest accuracy, while Emerald showed the most deviation in accuracy for single crown preparations.